System Level Modelling of RF IC in SystemC-WMS. (21st April 2008) - Orcioni, Simone; Ballicchia, Mauro; Biagetti, Giorgio; d'Aparo, Rocco D.; Conti, Massimo
Abstract : This paper proposes a methodology for modelling and simulation of RF systems in SystemC-WMS. Analog RF modules have been described at system level only by using their specifications. A complete Bluetooth transceiver, consisting of digital and analog blocks, has been modelled and simulated using the proposed design methodology. The developed transceiver modules have been connected to the higher levels of the Bluetooth stack described in SystemC, allowing the analysis of the performance of the Bluetooth protocol at all the different layers of the protocol stack.